2006
DOI: 10.1590/s1806-37132006000600009
|View full text |Cite
|
Sign up to set email alerts
|

Fibrose maciça progressiva em trabalhadores expostos à sílica: achados na tomografia computadorizada de alta resolução

Abstract: Objective: To evaluate the radiological characteristics of conglomerate masses using high-resolution computed tomography of the chest. Methods: From among the patients treated between 1986 and 2004 at the Antonio Pedro University Hospital, 75 patients with silicosis and massive fibrosis, most working in the field of sandblasting, were selected for study. These patients were submitted to a clinical evaluation, chest X-ray and high-resolution computed tomography of the chest. Results: In more than half of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 12 publications
4
14
0
1
Order By: Relevance
“…The finding of eggshell calcification on an HRCT scan was rare in this study. (8) The result, however, agrees with the literature, in which punctuated or uniform calcification is more frequently described, differing from the findings of Ferreira et al (1,9) Various studies have demonstrated the importance of standardization in the reading of HRCT scans, aiming at decreasing the differences in findings among readers, principally when the focus is the profusion and extent of the lesions. The use of a standardized reading protocol based on Bégin et al (10) has certainly contributed to the high indices of concordance in relation to the diagnosis of silicosis among the readers in the study conducted by Antão et al (8) Since the 1990s, radiologists have proposed standardized protocols for this type of reading, aiming to decrease the variability among the readers and to create the possibility of comparing clinical and epidemiological studies in the area, similarly to what has been done with the simple chest X-ray since 1930.…”
Section: Silicosis (Still) Among Us Eduardo Mello De Capitanisupporting
confidence: 73%
See 2 more Smart Citations
“…The finding of eggshell calcification on an HRCT scan was rare in this study. (8) The result, however, agrees with the literature, in which punctuated or uniform calcification is more frequently described, differing from the findings of Ferreira et al (1,9) Various studies have demonstrated the importance of standardization in the reading of HRCT scans, aiming at decreasing the differences in findings among readers, principally when the focus is the profusion and extent of the lesions. The use of a standardized reading protocol based on Bégin et al (10) has certainly contributed to the high indices of concordance in relation to the diagnosis of silicosis among the readers in the study conducted by Antão et al (8) Since the 1990s, radiologists have proposed standardized protocols for this type of reading, aiming to decrease the variability among the readers and to create the possibility of comparing clinical and epidemiological studies in the area, similarly to what has been done with the simple chest X-ray since 1930.…”
Section: Silicosis (Still) Among Us Eduardo Mello De Capitanisupporting
confidence: 73%
“…(4) In view of this joint effort of dissemination of knowledge about the disease among us (physicians and other health professionals), any support in terms of information and discussion regarding silicosis is always welcome. This is the case of the study conducted by Ferreira et al, (1) which brings information on cases, mostly in individuals working in the field of sandblasting, that reinforces the findings of high-resolution computed tomography (HRCT) of the chest, findings characteristic of accelerated silicosis with massive fibrosis (large opacities). These characteristics, when detected in a specific clinical case, assure the pulmonologist, radiologist or occupational physician that the individual has this form of silicosis, thereby avoiding investment and risks related to invasive procedures normally used in the presence of lung masses.…”
Section: Silicosis (Still) Among Us Eduardo Mello De Capitanisupporting
confidence: 62%
See 1 more Smart Citation
“…In silicosis patients, excluding the coexistence of active tuberculosis is extremely important, because this would indicate a treatment other than chemoprophylaxis [3]. Establishing a diagnosis of tuberculosis in these cases can be difficult, and the presence of systemic symptoms should raise the suspicion of associated infection [18]. We suspected silicotuberculosis in our case, because the patient had a previous history of tuberculosis associated with a one-month history of productive cough and hemoptysis, and the computed tomography showed cavitation of the conglomerate mass.…”
Section: Discussionmentioning
confidence: 99%
“…We suspected silicotuberculosis in our case, because the patient had a previous history of tuberculosis associated with a one-month history of productive cough and hemoptysis, and the computed tomography showed cavitation of the conglomerate mass. In a series of 44 patients [18] with silicosis and conglomerate masses who underwent chest HRCT, cavitations were noted in 8 patients, and of these, 6 had concomitant tuberculosis. Occasionally, cavitation due to ischemic necrosis may occur in a conglomerate mass [1, 2].…”
Section: Discussionmentioning
confidence: 99%